Pengaruh Media Dan Intensitas Naungan terhadap Pertumbuhan Bibit Tancang (Bruguiera gymnorrhiza (L.) Lamk.) - Cecep Kusmana; Yolan Yussy Sukaesih (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
Bruguiera gymnorrhiza is a mangrove species that can be used to rehabilitate mangrove forest. The information about the response of mangrove seedlings to the factors that affect its growth is needed to ensure its survival rate. This study aimed to examine the response of Bruguiera gymnorrhiza seedlings to the factors that affect its growth such as media and shade level. This research used a Completely Randomized Factorial Design (CRFD) with the treatments of growing media (A) and shade level (N) of 3 levels on each factor, that are mud (A0); mud and compost (A1); and mud, compost, sand (A2); also 0% shade (N0); 50% shade (N1); and 70% shade (N2) on the 3 months old seedlings. The results showed that the treatment of shade level significantly affected the growth response of B. gymnorrhiza seedlings, while the treatment of growing media and interaction of both treatments did not show a significant response. The 0% shade level gave the best growth response of B. gymnorrhiza seedlings. Keywords: Growth rate, light level, mangrove, rehabilitation, seedbed